THE ROLE OF ASAHAN POLICE INVESTIGATORS IN CRIMINAL ACTS OF DOMESTIC VIOLENCE CASE - Imelda Mardayanti; Haikal Iskandar Hashina Harahap; Ismail Ismail (UNISSULA, 2022)
The purpose of writing this research is to find out and describe the data that after being explained earlier shows that the settlement of cases of domestic violence is very important that is enforced by the police investigators, the approach method used uses a socio-legal approach, the results of the study state that the protection of victims of domestic violence at the Unit The PPA of the Asahan Police is carried out by maximizing the role of the Asahan Police Investigator in eliminating Domestic Violence. Among the legal innovations carried out beyond Act No. 23 of 2004 concerning the Elimination of Domestic Violence, especially law enforcement officers such as the Police, Advocates and courts in providing services and protection for victims of domestic violence, especially beyond setting up protection mechanisms in courts for the safety of victims, namely regarding protection mechanisms in courts for the safety of victims.